Study on MHD Cylindrical Couette Flow and Rheological Properties of Some Magnetic Suspensions - E. Hamza, S.E. (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The study of magnetic suspensions (MS) and magnetic field effects on their rheological properties is of evident practical importance due to its ability to orient and change their physical properties, especially their viscosity, by magnetic fields. This research presents the effect of a uniform magnetic field on the flow of MS in the annular region between two concentric cylinders. The motion of the fluid is due to the rotation of the inner cylinder with a constant angular velocity. An exact solution of the governing equations is obtained in the form of modified Bessel functions of the first and second kinds. The torque, which must be applied to the inner cylinder in order to maintain the rotation, is also calculated. The results show that as the magnetic parameter increases, the velocity profile decreases, while the torque increases due to the effect of magnetic force against the flow direction. In order to model the magnetoviscous effects, experiments were performed for different shear rates and different magnetic field strengths by using specially designed rheometers. The studied samples are iron oxide-water-glycerol system, ferrofluid nanoparticles, MAG DX biocompatible ferrofluid. The theoretical analysis is based on Giesekus model for MS. This model gives more accurate results and takes into account the effects of viscoelastic shear thinning characteristics. It is found that a magnetic field increases the viscosity of all suspensions under consideration. Finally, new proposed correlation for the viscosity of MS as a function of both shear rate and magnetic field has been suggested.